The Role of Profauna to Fight Illegal Logging in Indonesia - Kusnadi, Iwan Henri; Hikmawan, M Dian (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to find out the way or role of non-governmental organizations or Profauna Indonesia's NGOs in eradicating or preventing illegal logging or logging in Indonesia. To examine this theme, this study uses two theories namely environmental politics and new social movements. Illegal logging in Indonesia itself is already at a pretty severe stage, according to data from the Ministry of Environment and Forestry (KLHK) in 2018 the state must lose Rp. 17.8 trillion, which until now the forests in Indonesia have reached the figure 82 to 85 million hectares alone, but the government continues to argue by saying Indonesia's forests currently still exist at 120 million hectares. To overcome this illegal logging, Profauna Indonesia has taken some ways including creating a Profauna Ranger Group that aims to protect forests in Indonesia.